2021
DOI: 10.1186/s12902-021-00784-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapy on glucose and lipid metabolism in peri- and postmenopausal women with a history of menstrual disorders

Abstract: Background Previous studies have indicated that women with a history of menstrual disorders have an increased risk of metabolic and cardiovascular diseases. This has been attributed to the high proportion of polycystic ovary syndrome (PCOS) among this group. The favorable effects of hormone replacement therapy (HRT) on serum lipid profiles and glucose homeostasis in postmenopausal women is widely accepted. Whether HRT can also show positive effects on metabolic homeostasis in menopausal women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…First, the main reason may be related to the fact that the majority of women diagnosed with prediabetes in this study were postmenopausal women (about 70% of women were over 50 years old). It is well known that estrogen is an important regulator of IR, and postmenopausal women are more prone to lipid disorders due to the lack of estrogen (41,42), which in turn causes central fat deposition and abdominal obesity in postmenopausal women (43)(44)(45), and harmful lipid deposition promotes the development of prediabetes. Additionally, the literature reported that women are inherently more prone to IR, but sex hormones, environment, and good lifestyle factors can improve the "genetic disadvantage" of women (46).…”
Section: Discussionmentioning
confidence: 99%
“…First, the main reason may be related to the fact that the majority of women diagnosed with prediabetes in this study were postmenopausal women (about 70% of women were over 50 years old). It is well known that estrogen is an important regulator of IR, and postmenopausal women are more prone to lipid disorders due to the lack of estrogen (41,42), which in turn causes central fat deposition and abdominal obesity in postmenopausal women (43)(44)(45), and harmful lipid deposition promotes the development of prediabetes. Additionally, the literature reported that women are inherently more prone to IR, but sex hormones, environment, and good lifestyle factors can improve the "genetic disadvantage" of women (46).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced estrogen production affects sexual function directly, and regular intake of HRT can improve that. Different studies have focused on its role, which showed its effect on fasting plasma glucose levels, low-density lipoprotein, and total cholesterol in peri- and postmenopausal women [ 50 ]. HRT enhances sexual function in a statistically significant way; hence the level of sexual satisfaction is better in postmenopausal women with HRT than those without HRT [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that HRT had no significant impact on the lipid profile, and some women still developed dyslipidemia despite HRT. [4] Other findings from large randomized trials also do not confirm the benefit of estrogen therapy for the prevention of cardiovascular disease, and HRT is not recommended for this purpose in clinical practice. [7] Clinically, we also found that by using HRT, although FSH decreased, no effect on the lipid profile was found.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that hormone replace therapy (HRT) had no significant impact on lipid profiles. [ 4 ] Recent studies focus on the association between FSH and cardiometabolic factors including serum lipids, but the results are controversial whether FSH is negatively or positively associated with dyslipidemia in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%